The relevance of sludge generated in wastewater biological treatment systems, with an emphasis on Ribeirão Preto, São Paulo, Brazil - da Silva Oliveira, Aline; Nikaido, Meire; Smidt Celere, Marina; Segura-Muñoz, Susana Inés (O Mundo da Saúde, 2020)
Sewage treatment has been an important issue for public health and for environmental pollution control. It is necessary to take into account that the elements present in urban and industrial wastewater have microbiological components and also have different chemical compounds that can affect human health. Among those chemical constituents, heavy metals present in the wastewater can contaminate the receptor rivers if they are not properly removed, representing a risk for human and environmental health. The present work aims to discuss Biological Wastewater Treatment and the need to evaluate heavy metals present in the generated sludge, taking into account its potential land application for soil quality improvement. Also, Ribeirão Preto’s Wastewater Treatment Station is presented and its importance for public health and for preservation of hydrological resources in the region is pointed out.